Extending laser plasma accelerators into the mid-IR spectral domain with a next-generation ultra-fast CO2 laser. (22nd January 2016) - Pogorelsky, I V; Babzien, M; Ben-Zvi, I; Polyanskiy, M N; Skaritka, J; Tresca, O; Dover, N P; Najmudin, Z; Lu, W; Cook, N; Ting, A; Chen, Y-H
Abstract: Expanding the scope of relativistic plasma research to wavelengths longer than the λ /≈ 0.8–1.1 μ m range covered by conventional mode-locked solid-state lasers would offer attractive opportunities due to the quadratic scaling of the ponderomotive electron energy and critical plasma density with λ . Answering this quest, a next-generation mid-IR laser project is being advanced at the BNL ATF as a part of the user facility upgrade. We discuss the technical approach to this conceptually new 100 TW, 100 fs, λ = 9–11 μ m CO2 laser BESTIA (Brookhaven Experimental Supra-Terawatt Infrared at ATF) that encompasses several innovations applied for the first time to molecular gas lasers. BESTIA will enable new regimes of laser plasma accelerators. One example is shock-wave ion acceleration (SWA) from gas jets. We review ongoing efforts to achieve stable, monoenergetic proton acceleration by dynamically shaping the plasma density profile from a hydrogen gas target with laser-produced blast waves. At its full power, 100 TW BESTIA promises to achieve proton beams at an energy exceeding 200 MeV. In addition to ion acceleration in over-critical plasma, the ultra-intense mid-IR BESTIA will open up new opportunities in driving wakefields in tenuous plasmas, expanding the landscape of laser wakefield accelerator (LWFA) studies into the unexplored long-wavelength spectral domain. Simple wavelength scaling suggests that a 100 TW CO2 laser beam will be capable of efficiently generating plasma 'bubbles' a thousand times greater in volume compared with a near-IR solid state laser of an equivalent power. Combined with a femtosecond electron linac available at the ATF, this wavelength scaling will facilitate the study of external seeding and staging of LWFAs.